Is Compassion a Good Career Move?: Nonprofit Earnings Differentials from Job Changes - Andrew C. Johnston; Carla Johnston (Institute of Labor Economics (IZA), 2020)
We explore the nonprofit earnings penalty. To separate the influence of demand and supply, we leverage workers who change employers in administrative tax data. The average nonprofit worker earns 5.5 percent less than the average for-profit worker. Supply-side factors (worker selection) contribute 80 percent of the nonprofit differential. The remaining 20 percent is from demand (a nonprofit penalty). Within-worker nonprofit variation generates several insights about the influence of nonprofits on the labor market. Nonprofits compress the wage distribution and reduce inequality among earners. Nonprofit penalties are much more pronounced in classic charities than in "commercial" nonprofits, which sometimes exhibit nonprofit premia.
Keywords: J4; J31; L3; 330; nonprofits; for-profits; employment; earnings; labor demand